Novel development tool for IEC 61499 based on domain-specific languages. Issue 2 (2022) - Sorokin, Radimir; Patil, Sandeep; Vyatkin, Valeriy
Abstract: This paper presents an example of a systematic approach based on domain-specific languages to implement Function Blocks Modelling Environment (FBME): an integrated development environment (IDE) for the international standard IEC 61499. The new open development environment for the standard of growing importance in the Industry 4.0 realm would contribute to the broader adoption of open standard-based development practices and facilitate efficient automation software development.